Teacher interpersonal behavior in the context of positive teacher-student interpersonal relationships in East Asian classrooms: Examining the applicability of western findings. (November 2019) - Sun, Xiaojing; Pennings, Helena J.M.; Mainhard, Tim; Wubbels, Theo
Highlights: Aim: what teacher behaviors constitute positive relationships in East Asia/China? Chinese teachers' interpersonal behavior was rather dominant, friendly and stable. Previous Western findings are not directly generalizable to East Asian contexts.